Application of Drone System for Land Cover Changes in Tembila Mangrove Forest and Pasir Akar Farm - Saiful Iskandar, Khalit; Noor Afiza, Badaluddin; Nurul Aini, Kamaruddin (2018)
The aim of this study is to determine the application of drone system for land cover changes in Tembila mangrove forest and Pasir Akar farm. This study was to compare land cover changes at Tembila mangrove forest and Pasir Akar farm within 10 years. This study also use another tool to determine land cover which is Google Earth Pro for providing data in 2007, 2012 and 2017. The data collected from the drone and was being analysed using Pix4d Mapper Pro and Drone Deploy in order to obtain the Normalized Difference Vegetation Index (NDVI), orthomosaic image and elevation. The results show that there are changes in land cover at Tembila mangrove forest and Pasir Akar farm. The total area of Pasir Akar farm is 0.27 km2 meanwhile for Tembila mangrove forest is 0.86 km2. For Pasir Akar farm, the changes from 2007 until 2017 is 98.84 % meanwhile for Tembila mangrove forest is 59.30 %. This land cover changes happened in Pasir Akar farm due to agricultural and livestock activity meanwhile in Tembila mangrove forest due to aquaculture and palm oil planta-tion.